A differentiated Indonesian language teaching module to strengthen thingking critical dimension of the Pancasila student profile in junior high school - Ariyana, Ariyana; Anggraini , Nori (BAHASTRA, 2026)
This study aims to analyze the implementation of a differentiation-based Indonesian language teaching module to strengthen the critical thinking dimension of the Pancasila Student Profile within the framework of the Independent Curriculum. This research employed a qualitative approach using a case study design to gain an in-depth understanding of classroom practices and teachers’ experiences in implementing differentiated learning. The study was conducted with ninth-grade students at State Junior High School 2 Mekar Baru, Tangerang Regency. The participants included two Indonesian language teachers, one school headmaster, and fourth-grade students involved in the learning process, with five students selected as interview participants through purposive sampling. Data was gathered by means of observing classroom activities, conducting semi-structured interviews, and analyzing documents such as teaching modules, lesson plans, and student work. The data were analyzed using the interactive model of Miles and Huberman, which involves data reduction, data display, and conclusion drawing. The findings revealed that the implementation of differentiation-based teaching modules supports student-centered learning and strengthens the critical thinking dimension of the Pancasila Student Profile, and teachers implemented various instructional strategies such as guided reading, storytelling, group discussions, and creative writing activities to accommodate students’ diverse learning needs. These practices increased student engagement, encouraged collaborative learning, and supported students in analyzing texts and expressing their ideas critically. However, several challenges were identified, including limited preparation time, large class sizes, and the need for additional teacher training. Overall, differentiation-based Indonesian language teaching modules have strong potential to support academic development and character education within the Independent Curriculum.